Development and Cross-National Validation of a French Version of the Jefferson Scale of Empathy for Students. Issue 3 (September 2022) - Gerbase, Margaret W.; Gustin, Marie-Paule; Bajwa, Nadia; Abbiati, Milena; Baroffio, Anne
Empathy is a multifaceted personal ability combining emotional and cognitive features modulated by cultural specificities. It is widely recognized as a key clinical competence that should be valued during professional training. The Jefferson Scale of Empathy for medical students (JSE-S) has been developed for this purpose and validated in several languages, but not in French. The aims of this study were to gather validity evidence for a newly developed version of the JSE-S and compare it between two French-speaking contexts. In total, 1, 433 undergraduate medical students from the universities of Lyon (UL), France and Geneva (UG), Switzerland participated in the study completing the JSE-S in French. Total and partial scores of the three subscales ("perspective taking, " "compassionate care" and "walking in patient's shoes") were calculated for each site. Construct validity of the JSE-S was analyzed considering three sources of evidence: content, internal structure and relations to other variables. A first-order Confirmatory Factor Analysis using structural equation modeling examined the three latent variables of the JSE-S subscales. Cronbach's α coefficients were 0.75 (UG) and 0.81 (UL). The items' discrimination power ranged between 0.29 and 1.60 (median effect size of 1.24). The overall correlations between items and total or partial scores derived from the latent JSE-S subscales were consistently similar in both study sites. Findings of this study confirm the latent structure of the JSE-S in French and its cross-national reproducibility. The comparable underlying structure of the questionnaire tested in two distinct French-speaking contexts endorses the generalizability of its measure.